Deficit Problem with the Fourth Industrial Revolution (International Journal of Innovative Research in Engineering & Management, 2023)
The Fourth Industrial Revolution, defined  by Klaus Schwab, founder and CEO of the Future  Economic Forum, envisions a world in which people  travel between digital domains and offline reality by  using technology linked in order to allow and control  their life. The first industrial revolution transformed our  lifestyle and economy from an agricultural and artisanal  economy to one dominated by industry and machinery. In  the second industrial revolution, oil and electricity  enabled mass manufacturing. In the third industrial  revolution, IT was utilized to automate manufacturing.  Every industrial revolution is typically seen as a distinct  event, but collectively they may be better viewed as a  sequence of events based on inventions of the previous  revolution and progressing to improved forms of  production. The main characteristics of the four industrial  revolutions, the possibilities of the 4th industrial  revolution and the difficulties of the 4th industrial  revolution are discussed in this paper. It is described in  this opinion piece, which is centered on the opinions of  some consultants, the most sensitive publications  submitted to and discussed at the Davos World Economic  Forum in 2016 upon that subject of this popular uprising,  and some predictions about the negative consequences of  a few really of the most short tenure in global  industrialization.
Keywords: Economic; Employment; Fourth Industrial Revolution; Technology; Vehicles